2013
DOI: 10.1186/1471-2458-13-418
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of selection bias in a health survey of children and families – the IDEFICS Sweden-study

Abstract: BackgroundA health survey was performed in 2007–2008 in the IDEFICS/Sweden study (Identification and prevention of dietary- and lifestyle-induced health effects in children and infants) in children aged 2–9 years. We hypothesized that families with disadvantageous socioeconomic and -demographic backgrounds and children with overweight and obesity were underrepresented.MethodsIn a cross-sectional study, we compared Swedish IDEFICS participants (N=1,825) with referent children (N=1,825) using data from Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…The number of 'drop-outs' was n = 5,187 (32% of total study population in T 0 ). Dropout analyses extensively reported before (16)(17)(18) showed that the percentage of overweight children, the mean BMI z-score and percentage body fat were slightly increased in the dropout group. This might be due to drop-outs having more often less educated parents, a migrant background and a lower well-being score.…”
Section: Procedures and Participantsmentioning
confidence: 72%
“…The number of 'drop-outs' was n = 5,187 (32% of total study population in T 0 ). Dropout analyses extensively reported before (16)(17)(18) showed that the percentage of overweight children, the mean BMI z-score and percentage body fat were slightly increased in the dropout group. This might be due to drop-outs having more often less educated parents, a migrant background and a lower well-being score.…”
Section: Procedures and Participantsmentioning
confidence: 72%
“…Second, an obvious limitation is that our cross-sectional design provided no basis for studying causality; whether the development of overweight and obesity was initiated before the divorce or whether the impact on the children's weight status was primarily attributed to marital conflict or the divorce. Third, one cannot exclude the possibility that a higher proportion of overweight children were absent from school on the day measurements were taken and were therefore over-represented among non-participants, which in turn could imply that children of divorced parents were under-represented in NCG, as previously stated 25. If so, the associations shown in this study could be underestimated, but, given that the children were recruited into the NCG by the school health service, selection bias is most likely not a big issue in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The first cohort included 1,825 children recruited from 2007 to 2008 who participated in the multicentre European Identification and Prevention of Dietary‐ and Lifestyle‐induced Health Effects in Children and Infants (IDEFICS) study . The second cohort was a register‐based population of 1,825 children matched to the IDEFICS population by municipality, gender and age , and was created for a study of possible selection bias in the Swedish IDEFICS study , using the unique personal identity number allocated to all Swedish residents . Complete cross‐sectional data from 2007 on parental education, family disposable income and parental national background were available for 3,647 of the 3,650 children.…”
Section: Methodsmentioning
confidence: 99%
“…Data on maternal BMI and smoking habits, the children's gestational age and diagnoses at birth were retrieved from the Medical Birth Register at the National Board of Health and Welfare . In addition, data on subsequent weight and height on the pooled study cohort were collected from records at child health centres and school health services during 2010 and 2011. Growth data were collected for the following ages: birth, 6 months, 1.0, 1.5, 2.5, 4.0, 5.5 and 8.0 years.…”
Section: Methodsmentioning
confidence: 99%